THE EFFECT OF ADDING CALCINED ALUMINA ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF ALUMINUM FOAM - Mohamed Amin Elsheemy; Ibrahim H Abdel Daiam; Refaie Omar; Yasser Abdelrhman (JES: Journal of Engineering Sciences, 2021)
In the last decades, Aluminum foam has attracted many researchers and manufacturers due to its unique properties which find a lot of applications, especially in a lightweight structure. The current work aims to study the effect of adding calcined alumina to the melting aluminum on the final mechanical and microstructure of produced aluminum foam. Calcium carbonate was used as a foaming agent. The study reveals that calcination times/temperature have a significant effect on the final foam porosity. with increasing calcination time from 30 min to 90 min the foam density improved from 2.27 to 1.27 g/cm3, which consequently result in increase of samples porosity from 15.9 to 52.7%. also, the results from the compression test show that the variation of calcination time can be used to alter the energy absorption capacity of samples. Tested samples achieved the highest energy absorption of 128 MPa at a calcination time of 90 min. Also, the study reveals that calcination temperature has a significant effect on the final foam porosity. with increasing calcination temperature from 400 to 800°C, the foam density improved from 2.18 to 1.09 g/cm3, which consequently result in increase of samples porosity from 18.94 to 52.79%. Tested samples achieved the highest energy absorption of 325 MPa at a calcination temperature of 800°C. The increase in porosity is measured by ImageJ software, and the energy absorption test was carried out by a quasi-static compression test. These improvements produced material can be used in applications needs high energy absorption like automotive industry.